2019
DOI: 10.1073/pnas.1812149116
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for achieving high speed and efficiency in biomolecular machines

Abstract: How does a biomolecular machine achieve high speed at high efficiency? We explore optimization principles using a simple twostate dynamical model. With this model, we establish physical principles-such as the optimal way to distribute free-energy changes and barriers across the machine cycle-and connect them to biological mechanisms. We find that a machine can achieve high speed without sacrificing efficiency by varying its conformational free energy to directly link the downhill, chemical energy to the uphill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 35 publications
4
58
0
Order By: Relevance
“…The location of the transition states was also found to affect the velocity. It was shown that kinesin moves faster when a transition state is close to the initial state [27][28][29][30]. The applied load increases the height of the kinetic barriers, making it more difficult to transition between states, and thus slowing down the velocity of the motor [28].…”
Section: Resultsmentioning
confidence: 99%
“…The location of the transition states was also found to affect the velocity. It was shown that kinesin moves faster when a transition state is close to the initial state [27][28][29][30]. The applied load increases the height of the kinetic barriers, making it more difficult to transition between states, and thus slowing down the velocity of the motor [28].…”
Section: Resultsmentioning
confidence: 99%
“…It may have been evolutionarily advantageous to optimize speed, efficiency, or some other property. A two-state kinetic model has been developed that describes a broad range of such motors by allowing for evolutionary DOFs, such as where the kinetic barrier steps happen in the motor cycle (85). By fitting these few parameters in simple models to nearly a dozen different biomolecular motors and pumps, we can learn what, if anything, is optimized and might serve as a fitness quantity.…”
Section: Protein Motors and Pumps Can Trade Off Speed Versus Efficiencymentioning
confidence: 99%
“…Since the three characteristic functions (see Equations (24), (28) and (31)) are determined by three parameters (∆, q and η) and a variation of ∆ = µ 1 − µ 4 (this can be achieved assuming a variation of the substrate and the end-product concentrations), the thermodynamic properties could improve because these characteristic functions are proportional to ∆. The latest could be the reason why some biomolecular machines can achieve high speed without sacrificing efficiency [36]. Now, from Equations (33), (34) and (35), it is clear that the efficiency that maximizes some of the characteristic functions is related only to q, so at the end, the thermodynamic properties are related to the degree of coupling providing the basis for comparing different types of coupling in a two-flow system.…”
Section: Discussionmentioning
confidence: 99%